NATIONAL IDENTITY OF THE SOVIET GERMANS IN DAYS OF THE GREAT PATRIOTIC WAR AND LIFE IN A SPECIAL SETTLEMENT («SPETSPOSELENIYE») IN 1942-1956 (BASED ON THE MATERIALS OF MOLOTOVSKY (PERM) AREA) - Subbotina, E.S. (Perm Federal Research Centre Journal, 2015)
The article considers the memoirs of the Soviet Germans devoted to mobilization into a labour army (1942-1956) beginning with the process of deportation and until partial rehabilitation of this national group. Memoirs are investigated for the purpose of eliciting possible concepts, words, and phrases which reflect and characterize their national identity.